Pull motivation factors of tourists on marine protected area - Chavez, Jeanifer H.; Flores, Chessa M.; Garces, Roi Jenesy G.; Machon, Lauriz D.; Monserate, Joseph Edward T.; Panadero, Maria Lizette D.
Tourism of marine protected area (MPAS) is a niche in tourism industry that promotes coastal sustainability. Knowing tourist motivation can help in tourism planning and policy making towards sustainable ecotourism of MPAs. The purpose of this study is to understand the pull motivation factors of tourists in a marine protected area. for this study, a quantitative approach was adopted to understand the pull motivation factors of MPA tourists. An anonymous questionnaire with four parts was designed for the data collection and analysis. Convenience sampling was used in the study. A total of one hundred eleven participants were included in this study. Data gathering was conducted in two weekends: April 1-2, 2017 and April 8-9, 2017. The results showed that the significant pull motivation factors for MPA tourists are "Comfort/Relaxation", "Environment" and "Education". The results of the study is supportive of the primary objective of ecotourism of MPA which is to spread awareness and educate people regarding environmental conservation.